Incidencia del Metarhizium anisopliae sobre la entomofauna benéfica de cultivos de maíz bajo condiciones de campo controladas en la ESPAM MFL - Sánchez Bravo, Juan Gabriel (2021)
The objective of the research was to evaluate the incidence of Metarhizium anisopliae on the beneficial entomofauna of maize under controlled field conditions at ESPAM. The study was experimental and field-based, comprising three stages. The first stage consisted of the establishment of Metarhizium anisopliae concentrations by means of: soil preparation (tillage and fertilisation), delimitation of plots under a DBCA, experimental sowing, characterization of the entomofauna, control of experimental conditions, obtaining and reactivation of Metarhizium anisopliae in the laboratory, and inoculation, 15 days after maize germination (T0: 0.00; T1: 0.5; T2: 1.00; and T3: 1.5 g/l). In stage 2, the impact on beneficial entomofauna was determined by estimating parasitism and mortality, supported by statistical tests (ANOVA and Tukey). The last stage involved the development of a field guide for the procurement, multiplication and application of Metarhizium anisopliae. The results showed a total of 17 species associated with the experimental crop: 8 from the order Hymenoptera, 4 from Hemiptera, 2 from Lepidoptera, and 1 each from Araneae, Coleoptera, Mantodea, and Lepidoptera. Metarhizium anisopliae was found to affect 8 beneficial species; T3 being more lethal and T2 less lethal. There was significance (p<0.05) between treatments, particularly in T3. In T2 and T1, the mortality rate did not exceed 20%, which allows us to accept the study hypothesis. It is concluded that, at higher doses, Metarhizium anisopliae significantly affects the beneficial entomofauna of the maize crop.